1982
DOI: 10.1038/clpt.1982.157
|View full text |Cite
|
Sign up to set email alerts
|

The caffeine CO2 breath test: Dose response and route of N-demethylation in smokers and nonsmokers

Abstract: The optimal conditions for performing the caffeine CO2 breath test (CBT) were investigated in smokers and nonsmokers. Caffeine labeled with 13C or 14C in all three (1, 3, and 7) methyl groups or specifically in the 1-, 3-, or 7-methyl groups were orally administered to healthy adults and the expiration of labeled CO2 was measured for 8 or 24 hr. The absolute rate of labeled CO2 excretion from trilabeled caffeine was proportional to the dose up to 3 mg/kg in all subjects. In smokers, the rate of labeled CO2 exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
4

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 3 publications
4
73
0
4
Order By: Relevance
“…For the CYP1A2 substrate [ 13 C]-caffeine, Park et al observed a significant correlation between 1 h single DOB 13 CO 2 / 12 CO 2 ratios and plasma [ 13 C]-caffeine clearance [132]. These results were in agreement with previous studies, in which excellent correlations between caffeine breath test results and caffeine clearance were found [133][134][135][136].…”
Section: Exhaled Breathsupporting
confidence: 83%
“…For the CYP1A2 substrate [ 13 C]-caffeine, Park et al observed a significant correlation between 1 h single DOB 13 CO 2 / 12 CO 2 ratios and plasma [ 13 C]-caffeine clearance [132]. These results were in agreement with previous studies, in which excellent correlations between caffeine breath test results and caffeine clearance were found [133][134][135][136].…”
Section: Exhaled Breathsupporting
confidence: 83%
“…The 2-hr accumulative exhalation of labeled CO2 was the CBT parameter calculated, since it is the best monitor of caffeine clearance in the adult (20). The CBT data from the Michigan PBB cohort was compared to the CBT data from our control groups of healthy urban Ilinois adult smokers or nonsmokers without a history of PBB exposure (20,24).…”
Section: Caffeine Breath Thstmentioning
confidence: 99%
“…The caffeine substrate used to monitor caffeine 3-Ndemethylation in the CBT was [3-13C-methyl] caffeine (99% 3C) synthesized by Cambridge Isotopes (Cambridge, MA) or by A. N. Kotake (20). The labeled caffeine dose, 3 mg/kg (up to a maximal dose of 250 mg), was dissolved in 20 mL of sterile water and ingested by the volunteers, followed by ingestion of a 20-mL water wash of the container.…”
Section: Caffeine Breath Thstmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 It generally has been accepted that the 2-hour cumulative exhalation of labeled CO 2 represents the best parameter of caffeine clearance in the adult. 32 Our data suggest that a single 1-hour measure is equally informative and simplifies the test. Moreover, we have shown that this parameter is highly reliable in terms of its reproducibility in subjects with a normal or cirrhotic liver.…”
Section: Discussionmentioning
confidence: 98%